Aptamers for SARS‐CoV‐2: Isolation, Characterization, and Diagnostic and Therapeutic Developments. Issue 5 (12th May 2022) - Amini, Ryan; Zhang, Zijie; Li, Jiuxing; Gu, Jimmy; Brennan, John D.; Li, Yingfu
Abstract: The SARS‐CoV‐2 virus and COVID‐19 pandemic continue to demand effective diagnostic and therapeutic solutions. Finding these solutions requires highly functional molecular recognition elements. Nucleic acid aptamers represent a possible solution. Characterized by their high affinity and specificity, aptamers can be rapidly identified from random‐sequence nucleic acid libraries. Over the past two years, many labs around the world have rushed to create diverse aptamers that target two important structural proteins of SARS‐CoV‐2: the spike (S) protein and nucleocapsid (N) protein. These have led to the identification of many aptamers that show real promise for the development of diagnostic tests and therapeutic agents for SARS‐CoV‐2. Herein we review all these developments, with a special focus on the development of diverse aptasensors for detecting SARS‐CoV‐2. These include electrochemical and optical sensors, lateral flow devices, and aptamer‐linked immobilized sorbent assays. Abstract : Nucleic acid aptamers have been widely shown to be effective molecular recognition elements to bind protein targets. In response to the urgent need for diagnostics and therapeutics for COVID‐19, multiple labs around the world have rushed to create diverse aptamers that target two important protein biomarkers of SARS‐CoV‐2: the spike (S) protein and nucleocapsid (N) protein. These aptamers have been further exploited as diagnostic and therapeutic tools for the fight against COVID‐19.